Wake up, this is joburg - Zack, Tanya; Lewis, Mark; Prabhala, Achal (Duke University Press, 2022)
A single image taken from a high-rise building in inner-city Johannesburg uncovers layers of history-from its premise and promise of gold to its current improvisations. It reveals the city as carcass and as crucible, where informal agents and processes spearhead its rapid reshaping and transformation. In Wake Up, This Is Joburg, writer Tanya Zack and photographer Mark Lewis offer a stunning portrait of Johannesburg and personal stories of some of the city's ordinary, odd, and outrageous residents. Their photos and essays take readers into meat markets where butchers chop cow heads; the eclectic home of an outsider artist that features turrets and full of manikins; long-abandoned gold pits beneath the city, where people continue to mine informally; and lively markets, taxi depots, and residential high-rises. Sharing people's private and work lives and the extraordinary spaces of the metropolis, Zack and Lewis show that Johannesburg's urban transformation occurs not in a series of dramatic, wide-scale changes but in the everyday lives, actions, and dreams of individuals
Description based on online resource; title from PDF title page (publisher's Web site, viewed 07. Nov 2022)
Keywords: Photography / Photoessays & Documentaries; Entrepreneurship -- South Africa -- Johannesburg -- Pictorial works; Entrepreneurship -- South Africa -- Johannesburg; Informal sector (Economics) -- South Africa -- Johannesburg -- Pictorial works; Informal sector (Economics) -- South Africa -- Johannesburg; Photography, Artistic; Geschichte; Stadt; Johannesburg; Bildband